The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3324/haematol.2013.087205
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated measles virus controls pediatric acute B-lineage lymphoblastic leukemia in NOD/SCID mice

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nproducts inhibit replication and spread of MV. Deficiency in suppression of the type I IFN response in normal cells is part of the attenuated phenotype of vaccine strains of MV. 40,41 Many solid cancer cells are known to have a decreased IFN response (reviewed by Pitha 42 ), which can be exploited for oncolytic virotherapy. 43,44 It is unknown whether ALL cells have a deficient type I IFN response impacting on their response to viral infection, whether they harbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…These include: adult acute lymphoblastic leukemia and chronic lymphocytic leukemia [58,59], adult T cell leukemia/lymphoma [60], atypical teratoid rhabdoid tumor [61], breast cancer [44,62], cholangiocarcinoma [63], colorectal cancer [64], cutaneous T cell lymphoma [65], gliomas [66], head and neck squamous cell cancer [67], hepatoblastoma [68], hepatocellular cancer [51], lung cancer [64,69,70], malignant peripheral nerve sheath tumor [71], mantle cell lymphoma [72], medulloblastoma [53,73,74], melanoma [75,76], mesothelioma [77,78], multiple myeloma [47,79], non-Hodgkin’s lymphoma [80], osteosarcoma [81], ovarian cancer [52,82,83], pancreatic cancer [49,50,84], prostate cancer [45,85], renal cell carcinoma [86], rhabdomyosarcoma [87], and splenic marginal zone lymphoma [88]. …”
Section: Improving the Oncolytic Efficacy And Safety Of MV Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include: adult acute lymphoblastic leukemia and chronic lymphocytic leukemia [58,59], adult T cell leukemia/lymphoma [60], atypical teratoid rhabdoid tumor [61], breast cancer [44,62], cholangiocarcinoma [63], colorectal cancer [64], cutaneous T cell lymphoma [65], gliomas [66], head and neck squamous cell cancer [67], hepatoblastoma [68], hepatocellular cancer [51], lung cancer [64,69,70], malignant peripheral nerve sheath tumor [71], mantle cell lymphoma [72], medulloblastoma [53,73,74], melanoma [75,76], mesothelioma [77,78], multiple myeloma [47,79], non-Hodgkin’s lymphoma [80], osteosarcoma [81], ovarian cancer [52,82,83], pancreatic cancer [49,50,84], prostate cancer [45,85], renal cell carcinoma [86], rhabdomyosarcoma [87], and splenic marginal zone lymphoma [88]. …”
Section: Improving the Oncolytic Efficacy And Safety Of MV Strainsmentioning
confidence: 99%
“…To date, there have only been two oncolytic viruses that have achieved regulatory approval worldwide, based on phase III data; both involved intratumorally injected attenuated viruses. H101, an E1B attenuated adenovirus, was approved in 2005 in China after demonstrating superior response rates in combination with chemotherapy over chemotherapy alone in patients with squamous cell cancer of the head and neck or esophagus [5,6]. Similarly, talimogene laherparepvec (T-VEC), an oncolytic herpes virus (HSV1) engineered to produce granulocyte macrophage colony-stimulating factor (GM-CSF), demonstrated a superior durable response rate and promising overall survival in patients with melanoma, becoming the first oncolytic virus approved in the USA and Europe in 2015 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Within the rapid progress of new therapeutic strategies for the treatment of hematological malignancies, OVs continue to be a promising tool for effective treatments. Attempts to treat hematological malignancies with OVs have also included vesicular stomatitis virus (VSV) [ 40 , 41 ], live attenuated measles virus (MV) [ 42 , 43 ], oncolytic parvovirus [ 44 ], myxoma virus (MYXV) [ 45 , 46 ], and oncolytic poxvirus [ 47 , 48 ]. OVs have shown both advantages and limitations as therapy tools, including challenges and opportunities to improve treatment tolerability.…”
Section: Introductionmentioning
confidence: 99%
“…Studies employing MV as an oncolytic virotherapy agent have suggested that SLAMF1 is a therapeutic target in certain hematological diseases. For instance, in mouse models, this therapeutic strategy has been evaluated using attenuated MV to target certain acute lymphoblastic leukemia (ALL) [ 27 ]. Attenuated MV efficiently killed leukemia cells without affecting normal human blood cells and progenitors.…”
Section: Introductionmentioning
confidence: 99%
“…Attenuated MV efficiently killed leukemia cells without affecting normal human blood cells and progenitors. A few intravenous injections of attenuated MV were able to eradicate leukemic blasts [ 27 ]. Takeda et al reported higher susceptibility of lymphoma cells to attenuated therapeutic MV vaccine strain (CAM-70)-induced cytolysis due to elevated expression of SLAMF1 in these cells.…”
Section: Introductionmentioning
confidence: 99%